Impacts of Farmers Participation in Upscaling Technologies on Mungbean (Vigna radiata L.) Production in the South-Western Region of Bangladesh (The Agriculturists, 2015)
The study evaluated the farmers participatory methods of upscaling technologies for increasing mungbean production in the south-western region of Bangladesh. It was a descriptive survey study and data were collected by interviewing 120 sample farmers in DFID-Mungbean Project areas in Bangladesh. The participatory methods trailed in the project were farmers seed exchange program, demonstrations trials, agricultural training and workshops on mungbean production. However, farmers to farmers seed exchange program was identified as the most effective method. During the project phase, the farmers selected and adopted their preferred mungbean varieties, developed and practiced appropriate land preparation techniques along with improved post-harvest operations. Farmers participation in technology generation and upscaling resulted in increasing area and production of the mungbean many fold during 2004 to 2008. The average yield of mungbean was 1370 kg/ha and almost all framers obtained yields more than that of the national average of 705 kg/ha. Agricultural training, farm size and extension contact accounted for 83% of the total variation in upscaling technology and 90% of the variation in yield of mungbean. The extent of upscaling technology in terms of increase in area and yield of mungbean were associated with various participatory methods practiced by the farmers in the study area. The Agriculturists 2014; 12(2) 39-47